A survey on the adaptation to specific physical training using the investigation methods for competitive swimmers - Şalgău, Silviu (Arena-Journal of Physical Activities, 2018)
Purpose. This paper comes into help for the coaches, showing some investigation methods which can be easily applied by them, in the absence of the physician or biochemist (which are not assisting the training usually), in order to achieve a high level of adaptation to the specific effort, the training state and effort capacity, and also technical and tactics improvement. Methods. We assumed, as hypothesis, that the investigation methods, science-based, used periodically during the trainings lead to a good effort adaptability and improvement of performance capacity of sportsmen, the training being done at optimal quotes. The study was conducted during 2016, November through 2017, May, in the CSM Bacau Club section of the city’s Olympic Pool, on 8 teen subjects (male-3, female-5), with age – 15,5±1,85; the research methods were bibliographical study, testing, observational and statistics. Some investigation methods were chosen and described, together with the tests we considered fitted, our goal being a simple and concise reading of the results. Results. For the technical training subjects received the marks listed below (average ± standard deviation): at initial test (I) – 8,03±0,35, at the midlle test (M) – 8,53±0,22 and at the final test (F) – 9,10±0,21. At specific tests they gain the results: - time over 100m (T100(s)): I – 70,56±9,73 and F – 69,62±9,70; - average speed (Sm(m/s)): I – 1,43±0,20 and F - 1,49±0,17; - specific resistance (Rs): I - 1,00±0,16 and F – 0,89±0,05. Also we observe that the progression coefficient calculated (Cp(%)) was improved with 10,61±8,99